Rotavirus zoonotiska potential : kan infekterade föl smitta människa? - Lassa, Emma (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2011)

(untitled)
Rotavirus causes diarrhea in young mammals all over the world, including infant humans. The diarrhea leads to severe dehydration that can be fatal if left untreated. The dehydration can be treated with fluid therapy and the infection heals itself. Despite the relatively easy treatment half a million children under the age of five dies every year due to diarrhea caused by rotavirus.